Robotic pancreaticoduodenectomy after open Roux-en-Y biliary-enteric anastomosis: Technical insights (with video) - Zhongchuan Tian; Yan Li; Ming Li; Liang Li; Baoyong Zhou (Asian Journal of Surgery)
Technique: Robotic pancreaticoduodenectomy (RPD) presents a formidable surgical challenge for patients with a prior history of bilioenteric anastomosis. However, there are no reports in the literature of robotic pancreaticoduodenectomy after open bilioenteric anastomosis. This article offers a detailed description of the surgical technique employed in performing RPD on a patient who previously underwent open Roux-en-Y biliary–enteric anastomosis, aiming to treat a duodenal tumor. Results: The patient underwent a successful surgery with a total operation time of 320 min and an estimated blood loss of approximately 150 ml. Following the procedure, the patient experienced an uncomplicated recovery and was discharged from the hospital after a 14-day hospitalization period. Postoperative pathology revealed a moderately differentiated adenocarcinoma of the duodenum invading the entire layer of the bowel wall. Conclusions: RPD is a safe and viable option for patients with a history of complex abdominal surgery.